METAPHOR, PARALLELISM, AND EMOTIONAL LOAD AS STYLISTIC DEVICES IN POLITICAL DISCOURSE. - Xushvaqtova Mohira (TADQIQOTLAR, 2025)
Annotation.  This  article  provides  a  comprehensive  analysis  of  metaphor, parallelism, and emotional load as fundamental stylistic devices in political discourse. It  examines  the  functional  roles  these  devices  play  in  enhancing  the  clarity, persuasiveness,  and  effective  appeal  of  political  communication.  Drawing  upon qualitative analysis of speeches by prominent political leaders, the study elucidates the complex  interaction  between  linguistic  form  and  rhetorical  impact.  The  results contribute  to  a  deeper  understanding  of  how  these  stylistic  strategies  facilitate audience engagement and improve the efficacy of political messaging.